Caregiver Sleep and Patient Neutrophil Engraftment in Allogeneic Hematopoietic Stem Cell Transplant: A Secondary Analysis. Issue 1 (January 2018) - Sannes, Timothy S.; Mikulich-Gilbertson, Susan K.; Natvig, Crystal L.; Brewer, Benjamin W.; Simoneau, Teresa L.; Laudenslager, Mark L.
Abstract : Background: Caregiving for allogeneic hematopoietic stem cell transplant (Allo-HSCT) patients can be significantly burdensome. Caregiver well-being often mirrors patients' suffering. However, to our knowledge, this dyadic relationship has not been linked to patient outcome. Objective: Caregiver's objective and subjective sleep and overall distress before transplantation were hypothesized to be related to patient's time to engraftment in secondary analyses. Methods: Dyads (N = 124) were Allo-HSCT patients (mean [SD] age, 49.2 [12.7] years) and their caregivers (mean [SD] age, 52.7 [12.3] years). Caregiver's subjective sleep quality was measured via the Pittsburgh Sleep Quality Index, objective sleep was measured by actigraphy, and distress was measured by combining validated psychological measures. Results: Both caregiver reports of worse sleep ( β = .22; P < .05) and objective measurement of caregiver sleep patterns (higher sleep efficiency; less time awake after sleep onset) collected before engraftment significantly predicted shorter time to patient engraftment ( β values = −.34 and .29, respectively; P values < .05). Caregiver distress was unrelated to engraftment ( β = .14; P = .22). Conclusions: Despite limitations in available patient data, these findings appear to link caregiver well-being to patient outcome. This underscores the interrelatedness of the patient-caregiver dyad in Allo-HSCT. Future research should examine psychological and biomedical mediators. Implications for Practice: Given that caregiver well-being during the peritransplantation period was associated with patient outcome in this study, such findings highlight the need to address caregiver and patient well-being during Allo-HSCT. There may be potential to improve patient outcome by focusing on the caregiver, which nursing staff is well positioned to monitor.